BOOK REVIEW THE SPECTRA OF AUTHORITARIANISM IN SOUTHEAST ASIA - Sujatnika, Ghunarsa (Indonesia Law Review, 2020)
This book results from of a collaboration between SHAPE-SEA and academics/experts who focus on variants of authoritarian practices that hit countries in ASEAN. The discussion presented by the authors aims to identify, understand, and analyze the effects of authoritarian regimes on democratic life in ASEAN. In this regard, this book attempts to present how human rights and fundamental freedoms can be compromised, as well as how vulnerable groups are increasingly marginalized.